A generic approach yields organic solar cells with enhanced efficiency and thermal stability. Issue 2 (5th November 2022) - Gao, Mengyuan; Zhang, Kai; He, Chunyong; Jiang, Hanqiu; Li, Xiong; Qi, Qingchun; Zhou, Kangkang; Chen, Yu; Zhao, Wenchao; Ye, Long
Abstract: The use of deuterium are critical for promoting the fundamental understanding of aggregate materials and their new functions. Particularly, the solution structure of conjugated polymers can be hardly resolved without deuteration. However, studies about the isotopic effects of casting solvents on the aggregated structures of photovoltaic polymers and their bulk‐heterojunction blends are deficient. Here, the impact of deuterated solvents on the thermal behavior, aggregated structures, and device performance of photovoltaic polymers is clearly delineated for the first time by multiple techniques. The enhanced π‐π stacking order of photovoltaic polymers is highly relevant to their relatively poor miscibility with deuterated solvents. Benefiting from higher crystallinity and optimized morphology of deuterated solvents processed films, the devices are able to achieve better efficiency and notable improvement in thermal stability. Our results highlight the isotopic effects of solvents on the aggregated structure of conjugated polymer systems and reveal the potential of innovative approaches to fabricate thermally stable high‐efficiency solar cells. Abstract : The potential and implications of deuterated solvents in optimizing the film morphology and fabricating thermally stable high‐performance organic solar cells have been demonstrated for the first time. These deuterated solvents enable the establishment of comprehensive structure‐performance relationships of photovoltaic polymers, which will help advance the structural characterizations of organic electronics from solution to thin films.